KOLABORASI LINTAS SEKTORAL DALAM KESIAPSIAGAAN BENCANA BANJIR STUDI KASUS DI KABUPATEN ACEH TAMIANG - Azis Bustari; Laksono Trisnantoro; Mubasysyir Hasanbasri (Jurnal Online Keperawatan Indonesia, 2018)
BACKGROUND: Massive flood occurred in 85% of the Aceh Tamiang neighborhood in 2006. It occurred in almost villages in the district. The impact of the flood on the public health depends on the vulnerability and type of the flood. The morbidity rate of some diseases had increased during the flood. The cross-sectoral collaboration is applied on some reasons and as an effort to collaborate various sectors which exchange information, resources, activities, and other capabilities in order to attain their goals. The expected outcomes can not be attained by those organizations or sectors when they work separately.OBJECTIVE: The research aimed at identifying how the cross-sectoral collaboration was applied in Aceh Tamiang District in the effort of flood disaster mitigation and preparedness.METHOD: The research employed an explorative-case study design. The research subjects were the officers having crucial roles in the process of flood disaster mitigation and preparedness. Samples were gathered through purposive sampling. Data were collected through in-depth interview, documentation study and direct observation. The data were validated by triangulation among the resource, method and data.RESULT AND DISCUSSION: The commando leadership style of the Disaster Management Head was able to influence and motivate all institutions in government and private sectors. The communication among authoritative institutions was still weak and difficult due to lack of appreciation of the institutions, and sectoral egoistic factor and birocracy culture. The local government communicated the information and policy through formal meeting and dialogue. Simple organization structure and machinery birocracy did not work well optimally in the effort of flood mitigation. Public involvement in formulating the local policy was still low.CONCLUSION: Commando leadership style and lack of harmony in the communication among institutions due to sectoral ego and birocracy arrogance made the simple structure and machinery birocracy not work optimally in the disaster mitigation. The public involvement was still low in formulating local policy on disaster.